Sikap dan Pengetahuan Masyarakat terhadap Money Politic dalam Pemilu Legislatif Tahun 2014 di Kabupaten Gowa - HL, Rahmatiah (Al-Daulah : Jurnal Hukum Pidana dan Ketatanegaraan, 2015)
Political money is very vulnerable to any election administration, including in legislative elections. This study aims to determine the extent to which attitudes and knowledge society Gowa to money politics. By using a questionnaire as a data collection was analyzed using simple regression analysis. The results show the people of Gowa tend to respond to the politics of money and this situation is conditioned by the stimulus of the candidates, knowledge of politics is low and the economic situation down to the middle is very difficult for the people of Gowa can avoid the politics of money, because it is a requirement unavoidable.